2008
DOI: 10.4049/jimmunol.180.12.8030
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibitors Enhance TRAIL-Induced Apoptosis through the Intronic Regulation of DR5: Involvement of NF-κB and Reactive Oxygen Species-Mediated p53 Activation

Abstract: Manipulation of TRAIL receptor 2 (DR5) pathway is a promising therapeutic strategy to overcome TRAIL-resistant lung cancer cells. Preclinical studies have shown that proteasome inhibitors enhance TRAIL-induced apoptosis in lung cancer cells, but the underlying mechanism has not been fully elucidated. In this study, we demonstrated the enhancement of TRAIL-mediated apoptosis in human alveolar epithelial cells by proteasome inhibitors that up-regulate DR5 expression. This effect was blocked by DR5-neutralizing A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 36 publications
8
45
1
Order By: Relevance
“…These findings corroborate the previous findings with curcumin (34), rosiglitazone (36), sulforaphane (35), proteasome inhibitors (33), and baicalein (37).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings corroborate the previous findings with curcumin (34), rosiglitazone (36), sulforaphane (35), proteasome inhibitors (33), and baicalein (37).…”
Section: Discussionsupporting
confidence: 83%
“…Previously, ROS have been implicated in induction of receptors by certain agents (33)(34)(35)(36)(37). Whether γ-T3 can generate ROS was examined by FACS.…”
Section: Dr5 and Dr4 Induction By γ-T3 Is Through Generation Of Rosmentioning
confidence: 99%
“…The transcriptional regulation of DR5 is complex and the multiple transcription factor binding sites of CHOP (CCAAT/ enhancer-binding protein-homologous protein), p53 and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), are present in the DR5 upstream region (26,27). Recently, it was also reported that p53 is a key regulator activating the extrinsic pathway through the induction of genes encoding transmembrane proteins such as DR4 and DR5 (18).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that increased phosphorylation of p53 at the Ser 392 position stabilizes the tetramer formation of tumor suppressor protein p53 (32). It has been shown that proteasome inhibitor MG132 increases the stability of p53 by enhancing the expression of p53 S-392 phosphorylation (33). It has also been shown that stress-dependent stabilization of p53 in the cytoplasmic pool targets p53 to locate in the mitochondria after monoubiquitylation (34).…”
Section: Discussionmentioning
confidence: 99%